Analysis of surface integrity and formation of material side flow in dry and wet machining of aluminum alloy - A. B., Hadzley; A. A., Anis; M. N., Farizan; M. H., Osman; T., Norfauzi; S., Noorazizi (UNIVERSITI TEKNIKAL MELAKA, 2018)
This paper presents the surface integrity of aluminum alloy under dry and wet conditions. Bars of aluminum alloy with consistent size have been machined at different cutting speeds and feed rates at very short cutting time. The comparison between dry and wet cutting have been assessed based on the surface integrity, determined by the surface roughness value and observation of surface profiles. The result shows that machining in dry condition produces better surface finish where the coolants did not give a big impact on the surface roughness especially at the higher cutting speed. Further observation at the surface profile of dry cutting shows that more formation of material side flow appeared on the machined surface that could decreased the surface roughness value. Surface generated under bot dry and wet conditions appeared with well-defined and free from other damage such as cracking or tearing.